Pengaruh Insentif dan Budaya Organisasi Terhadap Kepuasan Kerja Guru - Sestriani Sestriani; Tri Kurniawati (Jurnal Ecogen, 2019)
This study aims to determine the effect of incentives and organizational culture on teacher job satisfaction at SMK N 2 Bukittinggi. This study uses 3 variables, namely incentives, organizational culture and job satisfaction. The research instrument used was a questionnaire distributed to 94 teachers of SMK N 2 Bukittinggi taken using total sampling techniques. Furthermore, the data collected was analyzed using multiple regression analysis to see the most dominant component of its influence on teacher job satisfaction at SMK N 2 Bukittinggi. The results of this study indicate: First, there is a positive and significant effect of incentives on teacher job satisfaction. Second, there is a positive influence of organizational culture on teacher job satisfaction. Third, there is a positive influence and organizational culture on teacher job satisfaction. The results of this study are expected to be useful for increasing teacher job satisfaction through the incentives provided and the organizational culture that is applied. Keyword: incentives, organizational culture and job satisfaction